Moderation and mediation of the spirituality and subjective well-being relation - Sargent, Adam M., author; Dik, Bryan, advisor; Steger, Michael, committee member; Swaim, Randall, committee member; Snodgrass, Jeffrey, committee member (Colorado State University. Libraries, 2015)
The present study aims to replicate the finding that spirituality correlates positively with subjective well-being and examines important moderating and mediating variables within this relationship (Koenig and Larson, 2001; Hill and Pargament, 2003). First, spiritual affiliation (religious denomination) is tested as a moderating variable and is found to significantly moderate the positive relationship between spirituality and subjective well-being furthering the case that spiritual affiliation should be considered in this line of research. Next, social support, spiritual support, spiritual strivings, and meaning in life are tested as mediators of the relationship between spirituality and subjective well-being. Social support, spiritual support, and spiritual goals/strivings are not found to mediate the relation between spirituality and subjective well-being, but meaning in life fully mediates this relationship suggesting that meaning in life may play a key role in understanding the spirituality and subjective well-being relation. Finally, a combined mediated moderation analysis is tested with spiritual affiliation as the moderating variable and meaning in life as the mediating variable. Evidence for mediated moderation was not found. Implications for future research and clinical practice are discussed.
Keywords: mediator; religion; well-being; moderator; meaning; spirituality